Early vascular endothelial complications after hematopoietic cell transplantation: Role of the endotheliopathy in biomarkers and target therapies development - Ana Belén Moreno-Castaño; Ana Belén Moreno-Castaño; Ana Belén Moreno-Castaño; María Queralt Salas; Marta Palomo; Marta Palomo; Marta Palomo; Julia Martinez-Sanchez; Julia Martinez-Sanchez; Montserrat Rovira; Francesc Fernández-Avilés; Carmen Martínez; et al. (Frontiers in Immunology, 2022)
This work aims to review the role of endothelial dysfunction underlying the main complications appearing early after autologous and allogeneic hematopoietic cell transplantation (HCT). The endothelial damage as the pathophysiological substrate of sinusoidal obstruction syndrome (SOS) is well established. However, there is growing evidence of the involvement of endothelial dysfunction in other complications, such as acute graft-versus-host disease (aGVHD) and transplant-associated thrombotic microangiopathy (TA-TMAs). Moreover, HCT-related endotheliopathy is not only limited to the HCT setting, as there is increasing evidence of its implication in complications derived from other cellular therapies. We also review the incidence and the risk factors of the main HCT complications and the biological evidence of the endothelial involvement and other linked pathways in their development. In addition, we cover the state of the art regarding the potential use of the biomarkers of endotheliopathy in the prediction, the early diagnosis, and the follow-up of the HCT complications and summarize current knowledge points to the endothelium and the other linked pathways described as potential targets for the prevention and treatment of HCT-complications. Lastly, the endothelium-focused therapeutic strategies that are emerging and might have a potential impact on the survival and quality of life of post-HCT-patients are additionally reviewed.